2016
DOI: 10.7314/apjcp.2015.16.18.8053
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefit of Metformin as Treatment for Colon Cancer: the Evidence so Far

Abstract: Metformin is known as a hypoglycaemic agent that regulates glucose homeostasis by inhibiting liver glucose production and increasing muscle glucose uptake. Colorectal cancer (CRC) is one of the most common cancers worldwide, with about a million new cases diagnosed each year. The risk factors for CRC include advanced age, smoking, black race, obesity, low fibre diet, insulin resistance, and the metabolic syndrome. We have searched Medline for the metabolic syndrome and its relation to CRC, and metformin as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
1
13
0
1
Order By: Relevance
“…For example, in vitro and in vivo studies showed that insulin stimulates the growth of colorectal tumors in cell lines ( 6 ) and animal models ( 7 ). Additionally, metformin, a medicine used to regulate glucose homeostasis, suppresses the activity of obesity-related CRC cells ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in vitro and in vivo studies showed that insulin stimulates the growth of colorectal tumors in cell lines ( 6 ) and animal models ( 7 ). Additionally, metformin, a medicine used to regulate glucose homeostasis, suppresses the activity of obesity-related CRC cells ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Each year, there are over one million newly diagnosed cases and approximately 600,000 cases of colorectal cancer-associated mortality (2). The major risk factors of colorectal cancer are increasing age and lifestyle factors, and other risk factors include obesity, insulin resistance and metabolic syndrome (3). The survival of this disease has improved considerably, however, the 5-year relative survival for patients aged 65 years and older remains as low as 60% (2).…”
Section: Introductionmentioning
confidence: 99%
“… 3 Multiple risk factors of CRC include insulin resistance, obesity, low fiber diet, increasing age, black race, smoking, and metabolic syndromes. 3 …”
Section: Introductionmentioning
confidence: 99%